Tribological Bench and Engine Dynamometer Tests of a Low Viscosity SAE 0W-16 Engine Oil Using a Combination of Ionic Liquid and ZDDP as Anti-Wear Additives - Barnhill, William C.; Gao, Hong; Kheireddin, Bassem; Papke, Brian L.; Luo, Huimin; West, Brian H.; Qu, Jun (Frontiers in Mechanical Engineering, 2015)
We have previously reported an oil-miscible phosphonium-organophosphate ionic liquid (IL) with an effective anti-wear (AW) functionality when added to a base oil by itself or combined with a conventional zinc dialkyldithiophosphate (ZDDP) for a synergistic effect. In this research, we investigated whether this synergy manifests in formulated engine oils. An experimental SAE 0W-16 engine oil was generated containing a combination of IL and ZDDP with equal phosphorus contribution. The prototype engine oil was first evaluated using tribological bench tests: AW performance in boundary lubrication (BL) and friction behavior (Stribeck curves) in elastohydrodynamic, mixed, and BL. The forthcoming standard Sequence VIE engine dynamometer test was then conducted to demonstrate improved fuel economy. Results were benchmarked against those of another experimental engine oil with almost the same formulation except using ZDDP only without the IL (similar total phosphorus content). The IL-ZDDP formulation consistently outperforms the ZDDP-only formulation in friction reduction and wear protection, and results from the bench and engine tests are well correlated.